PENGARUH PROFESIONALISME AUDITOR INTERNAL TERHADAP TINDAKAN KECURANGAN PADA USP SWAMITRA BUKOPIN DI JAKARTA - Riko Sutriyadi; Elvin Shelly Joe (JURNAL LENTERA AKUNTANSI, 2021)
This study aims to find out how the Effect of Internal Auditor Professionalism on Fraudulent Actions. Internal auditors as people who carry out internal auditing activities, have an obligation to assist management in preventing fraudulent acts, through reviews of the effectiveness of internal controls and providing suggestions for improvement. Professionalism is a measure used to see how well a person carries out his work or profession. Good experience will produce better knowledge than those who do not have sufficient knowledge of the task. The data used in this study were obtained from a questionnaire created by the researcher and filled out by the Internal Auditor of USP Swamitra Bukopin in Jakarta. USP Swamitra Bukopin is a Savings and Loan Unit from the cooperation between the Cooperative and PT Bank Bukopin, Tbk. Based on the results of data analysis that has been carried out by the author at the USP Swamitra Bukopin in Jakarta, regarding the Effect of Internal Auditor Professionalism on Fraud, the authors can conclude that there is a significant positive effect between the X variables on Y, because the value of t-count > t-table (4,878 > 2,069). So that there is an influence between the X variable on Y, or in other words Ho accepts and Ha is rejected. Based on research conducted at USP Swamitra Bukopin in Jakarta, it can be concluded that the professionalism of internal auditors has a significant effect on fraud. Based on the calculation of the regression test, it can be seen that the coefficient of determination (R2) is 0.509 or 50.9%, which means that the contribution of the professionalism of the internal auditors to fraud at the USP Swamitra Bukopin in Jakarta is strong. While the remaining 0.491 or 49.1% is influenced by other factors that are not taken into account in this study.Keywords : Profesionalisme Auditor Internal dan Tindakan Kecurangan